2014
DOI: 10.1074/mcp.m114.038505
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced Changes to Integrin α 3 Glycosylation Facilitate Invasion in Epidermoid Carcinoma Cell Line A431

Abstract: Hypoxia is a critical microenvironmental factor that drives cancer progression through angiogenesis and metastasis. Glycoproteins, especially those on the plasma membrane, orchestrate this process; however, questions remain regarding hypoxia-perturbed protein glycosylation in cancer cells. We focused on the effects of hypoxia on the integrin family of glycoproteins, which are central to the cellular processes of attachment and migration and have been linked with cancer in humans. We employed electrostatic repu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 65 publications
(63 reference statements)
2
19
0
Order By: Relevance
“…The laminin from Engelbreth-Holm-Swarm (EHS) tumor used in this study is usually considered laminin-1 (Patarroyo et al, 2002). Integrin α 3 β 1 was originally identified as a promiscuos receptor for a range of ligands including collagen, fibronectin, entactin, laminin-5, thrombospondin-1 and the laminin used in this study, lamini-1 (Ren et al, 2014). Most integrins bind to several ECM molecules, and most ECM bind to more than one integrin heterodimer.…”
Section: Discussionmentioning
confidence: 99%
“…The laminin from Engelbreth-Holm-Swarm (EHS) tumor used in this study is usually considered laminin-1 (Patarroyo et al, 2002). Integrin α 3 β 1 was originally identified as a promiscuos receptor for a range of ligands including collagen, fibronectin, entactin, laminin-5, thrombospondin-1 and the laminin used in this study, lamini-1 (Ren et al, 2014). Most integrins bind to several ECM molecules, and most ECM bind to more than one integrin heterodimer.…”
Section: Discussionmentioning
confidence: 99%
“…In human epithelial carcinoma (A431), Ren et al reported that hypoxia-induced alterations to the glycosylation of ITGA3 prevented its efficient translocation to the plasma membran. This resulted in an enhanced invasive competence to cancer cells [97]. In another indirect correlation between PGs, integrins, and hypoxia, You et al showed that pericyte expression of NG2 (neuron glia antigen-2) is critical for its interaction with endothelial cells in a NG2 knockdown melanoma (B16F10 lineage) model.…”
Section: Alterations In the Cell–cell And Cell–extracellular Matrix Imentioning
confidence: 99%
“…Some studies have reported molecular changes promoted by the hypoxia microenvironment, but did not elucidate the functional consequences promoted by glycoconjugates alterations in neoplastic cells. However, some studies associated these modifications with cancer cell proliferation, migration, and survival, indicating that such glycoconjugates may be used as targets for further therapeutic strategies for cancer treatment [97-99]. …”
Section: Hypoxia Changes Membrane Glycoconjugates In Tumor Cellsmentioning
confidence: 99%
See 2 more Smart Citations